Charge Pair Separation Dynamics in Organic Bulk‐Heterojunction Solar Cells. Issue 7 (21st May 2018) - Albes, Tim; Gagliardi, Alessio
Abstract: Charge pair separation in organic bulk‐heterojunction (BHJ) solar cells is a complex interplay between numerous factors, such as the spatial geometry of the blend, the distribution of energetic disorder, the electric field, thermal fluctuations, and the mutual electron–hole Coulomb attraction. Insufficient separation from the interface and concomitant charge pair recombination is a main limitation in improving the PCE of organic BHJ solar cells and requires an in‐depth understanding of the timescales involved. Here, a 3D kinetic Monte Carlo model of a BHJ organic solar cell is set up and the time‐dependent evolution of mutual electron–hole pair distances separating from the heterojunction interface is investigated. Large fluctuations in separation times are found, in particular in dependence of the energetic disorder and the permittivity of the organic materials. At commonly observed values of energetic disorder, slight modifications of the permittivity can drastically influence the charge separation time and even outweigh orders of magnitude of geminate recombination rates, hence help to suppress geminate recombination. Thus, the results strongly support the recent trend of developing high‐permittivity organic materials for solar cell applications. Abstract : In bulk‐heterojunction organic solar cells, the charge pair separation competes against recombination for efficient generation of photocurrent. By utilizing kinetic Monte Carlo simulations, the separation times are explicitly extracted and put into relation to recombination times. It is shown that even slight changes in the dielectric constant of the materials can outweigh orders of magnitude of recombination times.